Analysing the Industrial Real Estate Market - Izabela RĄCKA (Communications of International Proceedings, 2020)
The industrial real estate market is a growing and dynamic market and there is a big difference between submarkets in terms of type of property or geographic area. As a rule, modern industrial properties are being leased, and they are the most often located in large cities, but for older properties, located in subregional areas, turnover is more common. There is a clear research gap in the analysis of sales transactions on the non-residential and non-agricultural market, especially in the segment of industrial real estate. Industrial are atypical properties, which means that when looking for similar properties in order to analyse the market, the spatial scope of the research should be extended. For this reason, the industrial submarket should be viewed more broadly and its analysis should cover the area of several neighbouring towns, districts or counties. The market analysis procedure was carried out starting from the observation of the market reality. Next we tried to find the coexistence of phenomena and establishing cause-effect relationships, after that we built a regression model. We built a database of nearly 100 records containing all transactions where the land was built-up with industrial plants in the southern part of Wielkopolskie Province in 2015-2019. The research showed that the prices of industrial real estate are influenced by: location, land area, type of space, date (year) of sale, type of buyer, type of seller, type of property rights. The study can help making investment decisions may be important for active participants of the industrial market.
Keywords: Commercial real estate; market analysis; valuation.